Early cataloguing of fragments from break-up events. Issue 10 (15th May 2023) - Pastor, A.; Siminski, J.; Escribano, G.; Sanjurjo-Rivo, M.; Escobar, D.
Highlights: Track association and correlation to build-up and maintain fragments orbits. Fragmentation objects coalescence at break-up epoch to reduce false positives. Analysis of the proposed approach with Cosmos 1408 anti-satellite test simulation. Abstract: Break-up events represent the dominant source of objects in space catalogues, surpassing half of the overall population. These not so uncommon events include explosions, collisions or anomalous events resulting in fragmentations and their number is estimated to be higher than 630. The early cataloguing of the fragments generated during these events poses a complex challenge for space objects catalogue build-up and maintenance processes. The provision of Space Surveillance and Tracking products and services during the few first days after a break-up event can be crucial to avoid collisions between the fragments and other space objects, particularly in highly congested regimes, such as Low Earth Orbit. In this regard, reducing the time required to accurately estimate the trajectories of the fragments may enable the execution of collision avoidance manoeuvres, in the case of operational space objects with manoeuvre capabilities, and analyse potential collision cascade events, which may endanger the space environment. This paper studies the whole cataloguing process after a break-up event, starting from a catalogue with no fragments from the fragmentation under-analysis, and until a well-established orbit is obtained for all fragments, using a ground-based sensor network. First, the observations enter a multi-sensor multi-target track-to-track association algorithm in charge of grouping observations belonging to the same objects. To resolve the ambiguity, particularly shortly after the event, hypotheses about tracks belonging to the same fragment are generated, scored, pruned, and promoted, only when there is enough confidence, leading to the initialisation of new objects in the catalogue. As soon as the catalogue is populated, a track-to-orbit correlation algorithm is responsible for the correlation of observations and already catalogued orbits. This alleviates the track-to-track association and enables the update of the orbital estimates, required for maintaining the catalogue.